Preface - Hassan, Arif (2014 Inderscience Enterprises Ltd. , UK, 2014)
This is an editorial note as the guest editor for the special issue of the Journal of Global Business Advancement, of vol. 7 (2) published in 2014. The papers included deals with the emerging challenges of various forms as a result of globalisation of the world economy. The special issue provides research based knowledge with the people from the industry and perhaps the government as policy makers, as well as to see whether the outcomes from the researches can be implemented in the real world. This in turn should encourage the advancement of theory and practice of global business.